Effects of wind, relative humidity, leaf movement and colony age on dispersal of conidia of uncinula necator, causal agent of grape powdery mildew - Willocquet, L.; Berud, F.; Raoux, L.; Clerjeau, M. (Wiley, 1998)
A wind tunnel was designed to study the effect of wind, relative humidity, leaf movement and colony age on dispersal of conidia of Uncinula necator. Wind speed as low as 2.3 m s−1 instantaneously triggered dispersal of conidia from fixed leaf discs of 18‐day‐old infections. Conidia were observed on sporulating leaf discs even after exposure to 17 m s−1 wind. The fraction of conidia dispersed at a given wind speed increased with colony age from 12 to 24 days. Conidia of 27‐day‐old colonies were less easily dispersed. No gradient of maturation of conidia along the conidial chain was observed, suggesting that even newly formed conidia were able to germinate after dispersal. Germination of dispersed conidia decreased slightly with greater colony age. Both wind and simulated rain drops caused dispersal of conidia from infected leaves. Leaf movement at wind speed of 3.5–4 m s−1 increased dispersal, and the first impact of three simulated raindrops caused release of 53% of the total conidia dispersed. Relative humidity had no effect on dispersal of conidia at different wind speeds.